Free ion diffusivity and charge concentration on cross-linked polymeric ionic liquid iongel films based on sulfonated zwitterionic salts and lithium ions. Issue 32 (5th August 2019) - Valverde, David; Garcia-Bernabé, Abel; Andrio, Andreu; García-Verdugo, Eduardo; Luis, Santiago V.; Compañ, Vicente
Abstract : The properties of various mixtures of a zwitterionic ionic liquid (ZIs-1 ) and LiNTf2, including their conductivity, have been studied showing how they can be adjusted through their molar composition. Abstract : The properties of various mixtures of a zwitterionic ionic liquid (ZIs-1 ) and LiNTf2, including their conductivity, have been studied showing how they can be adjusted through their molar composition. Conductivity tends to increase with the LiNTf2 content although it presents a minimum at the region close to the eutectic point. These mixtures also provide excellent features as liquid phases for the preparation of composite materials based on crosslinked PILs. The prepared films display excellent and tuneable properties as conducting materials, with conductivities that can be higher than 10 −2 S cm −1 above 100 °C. The selected polymeric compositions show very good mechanical properties and thermal stability, even for low crosslinking degrees, along with a suitable flexibility and good transparency. The final properties of the films correlate with the composition of the monomeric mixture used and with that of theZIs-1 :LiNTf2 mixture.